Operational Experience of Tritium Handling Facilities in the Japan Atomic Energy Agency's Tritium Process Laboratory. (19th May 2017) - Kurata, Rie; Yamada, Masayuki; Suzuki, Takumi; Nakamura, Hirofumi; Iwai, Yasunori; Isobe, Kanetsugu; Hayashi, Takumi
Abstract: Tritium Process Laboratory (TPL) in Japan is operated by the Japan Atomic Energy Agency (JAEA) and was established as the only facility to handle over one gram of tritium in Japan in 1985. Since March 1988, the TPL has been operated safely with tritium, and no tritium release accidents have been occurred. The maximum tritium concentration of a three-month average in a stream from a stack of TPL to environment was 350 Bq/m 3, and is about 14 times smaller than that of the legal release limit in Japan. The failure data have been analyzed for several main components of the safety systems such as pumps and monitors. The tritium waste data has also been accumulated as liquid and solid waste from TPL. Through this operating experience, a significant database for the safety systems of the TPL has been accumulated. This data can provide a source of reliability information for a future fusion facilities.